The trajectories of creative content protecting law in Indonesia: dealing with the challenge and advancing the potential - Yuspin, Wardah; Fauzie, Ata; Hermawan, Danny (Penerbit Universiti Kebangsaan Malaysia, 2019)
The article aims at determining the legal protection of creative content uploaded by the creators through online media as well as the challenges faced by the creators in protecting their works. This research includes descriptive normative of the legal research that describes the legal protection and the challenges faced by the creators in protecting their works. The secondary data are obtained from the case file of Agency France Presse v. Morel, Decision No. 68/HC/2005/PN.Niaga.Jkt.Pst, and Decision No. 056 PK/Pdt.Sus/2010. The collection of secondary data is done through literature study. Based on the results, it can be concluded that, first, United States copyright laws and the Digital Millennium Copyright Act (DMCA) have accommodated the protection of the works uploaded through online media even though they have not been registered in the relevant institution as demonstrated by the case of Agence France Presse v. Morel. Second, the Indonesian copyright law has some similarities to the articles of the DMCA used in the case of AFP v. Morel. Referring to the case No. 68/HC/2005/PN.Niaga.Jkt.Pst, in the case the copyright of the infringing logo has not been registered and it is registered by a party who is not the actual creator, it is decided that the registration can be cancelled with evidence presented at the trial. Several challenges faced in protecting creative content include the contractual relationships between users and service providers, the absence of copyright registration, and the characters of user in digital media. The terms of service set by service providers usually non-exclusive licenses or royalty free in which they can utilise the works in accordance with the existing provisions.